Balancing the strength and ductility of Ti2AlC/TiAl composite with a bioinspired micro-nano laminated architecture. (August 2022) - Liu, Pei; Hou, Bo; Wang, Aiqin; Xie, Jingpei; Wang, Zhenbo
Graphical abstract: Highlights: Ti2 AlC/TiAl composite with bioinspired micro-nano laminated architecture was fabricated. The composite consists of micro-laminated Ti2 AlC, micro-nano γ-TiAl/α2 -Ti3 Al lamellar colony and nano-laminated Ti2 AlC. The composite possesses a good combination of strength and ductility due to multiple plastic deformation features. Abstract: In this work, the Ti, Al and graphene flake powders were used as raw materials, and a Ti2 AlC/TiAl composite with the bioinspired micro-nano laminated architecture was successfully fabricated by spark plasma sintering and subsequent heat treatment. The as-fabricated composite mainly consists of the micro-laminated Ti2 AlC with the length of 300 μm and thickness of 15 μm, the micro-nano γ-TiAl/α2 -Ti3 Al lamellar colony with the average lamellar spacing of 0.8 μm, and the nano-laminated Ti2 AlC with the thickness of 10 nm. It was found that the composite possesses a good combination of compressive strength (1807 MPa) and ductility (25.5%) at room temperature due to its multiple plastic deformation features: i) dislocations and atomic-scale ripples could be easily nucleated on the (0001) basal plane of the micro-laminated Ti2 AlC; ii) the micro-laminated Ti2 AlC/TiAl interface could be the nucleation source for the dislocation and deformation twins; iii) high-density deformation twins could be formed in the γ-TiAl phase of γ-TiAl/α2 -Ti3 Al lamellar colony; iv) the pyramidal dislocation could be generated in the nano-laminated Ti2 AlC. The aim of this work is to enrich the current understanding on the deformation behavior of TiAl matrix composites and open up a novel design direction for high-performance TiAl matrix composites.